Octopus arm movements under constrained conditions: adaptation, modification and plasticity of motor primitives - Richter, Jonas N.; Hochner, Binyamin; Kuba, Michael J. (Journal of experimental biology, 2015)
The motor control of the eight highly flexible arms of the common octopus (Octopus vulgaris) has been the focus of several recent studies. Our study is the first to manage to introduce a physical constraint to an octopus arm and investigate the adaptability of stereotypical bend propagation in reaching movements and the pseudo-limb articulation during fetching. Subjects (N=6) were placed inside a transparent Perspex box with a hole at the center that allowed the insertion of a single arm. Animals had to reach out through the hole toward a target, to retrieve a food reward and fetch it. All subjects successfully adjusted their movements to the constraint without an adaptation phase. During reaching tasks, the animals showed two movement strategies: stereotypical bend propagation reachings, which were established at the hole of the Perspex box and variant waving-like movements that showed no bend propagations. During fetching movements, no complete pseudo-joint fetching was observed outside the box and subjects pulled their arms through the hole in a pull-in like movement. Our findings show that there is some flexibility in the octopus motor system to adapt to a novel situation. However, at present, it seems that these changes are more an effect of random choices between different alternative motor programs, without showing clear learning effects in the choice between the alternatives. Interestingly, animals were able to adapt the fetching movements to the physical constraint, or as an alternative explanation, they could switch the motor primitive fetching to a different motor primitive ‘arm pulling’.